A communicative act as a main unit of teaching Ukrainian as a foreign language - Кушнір, І. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2020)
The author, emphasizing the necessity of updating the content of the language education of non-philological foreign students of Ukrainian universities, performs a linguo-didactic analysis of the subject side of the content of the system of teaching Ukrainian as a foreign language to non-philological students. Within the modern linguistic paradigm, the subject content of teaching a foreign language, in particular UFL, is considered a system of linguistic means (phonetic, lexical, grammatical, stylistic, socio-cultural, speech etiquette, rhetorical). In the conditions when the modern linguodidactic paradigm is dominated by communicative-activity and intercultural approaches and the consciously-practical method of teaching, aimed at ensuring that foreign students would master the content component of their language education, the following units of learning are recognized: sentences, expressions, texts, and dialogues. The need for updating the content component of the teaching system of UFL arises in connection with the requirements of the modern information society and new requirements for the tasks and results of teaching foreign languages. It has been found that the achievements of a relatively new theory of language communication will allow refining the components of the content of foreign language teaching, which will have an impact on improving the quality of language education of foreign non-philological students of Ukrainian universities. The submitted scientific research substantiates the choice of such a unit of study as a communicative act, which in the future allows reforming the educational process to attract foreign students to Ukrainian discourses. The author describes the structural-semantic components of the personal, verbal-cognitive, verbal and extraverbal levels of the communicative act as a fragment of the communication process within a certain communicative situation. The conclusion is made about the potentialities of the described parameters of the communicative act as a basis for updating the steady methodical principles of language material selection.